Aldo-keto reductase activity after diethylhexyl phthalate exposure in eutopic and ectopic endometrial cells. (August 2017) - Kim, La Yeon; Kim, Mee Ran; Kim, Jang Heub; Cho, Hyun Hee
Abstract: Objective: Endometriosis is a multifactorial gynaecological disease in reproductive-age women. Endometriotic tissue is characterized by high prostaglandin levels and progesterone resistance. Human aldo-keto reductases (AKRs) convert progesterone to a less potent metabolite and cause progesterone resistance. Therefore, in this study, we evaluated whether diethylhexyl phthalate (DEHP) alters AKR expression in human ectopic and eutopic endometrium. Study design: We used microarrays and western blotting to study the effects of DEHP, and checked the presence of AKR in endometriosis patients by enzyme-linked immunosorbent assay (ELISA). Results: Cultured human endometrial cells from normal endometrium of women without endometriosis (NE), eutopic endometrium from endometriosis patients (EE), and ectopic endometrium from endometriosis patients (EC) differed in genetic expression changes after DEHP treatment. DEHP upregulated AKR1C1, AKR1C2, AKR1C3, and AKR1B10 expression in EE, while EC showed continuously increased AKR1C3 expression before and after DEHP exposure. In western blot analysis, before and after DEHP exposure, the AKR1B10 protein band was detected in NE, EE, and EC, whereas the AKR1C3 band was detected only in EC. AKR1B10 and AKR1C3 expression levels in the blood of the enrolled patients were evaluated using ELISA. AKR1B10 expression did not differ between groups (without endometriosis [N = 13], 0.10 vs. with endometriosis [N = 20], 0.11; P  = 0.27). AKR1C3 expression was significantly higher in the blood of endometriosis patients than in that of patients without endometriosis (without endometriosis, 9.1 vs. with endometriosis, 10.1; P  = 0.02). Analysis according to menstrual period showed significantly increased AKR1C3 levels in patients with endometriosis only during the secretory phase and not the proliferative phase (P < 0.05). Conclusion: DEHP induces AKR activity in the endometrium of endometriosis patients, and AKR1C3 might influence the development of endometriosis.